PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS KETIADAAN TRANSPARANSI INFORMASI DI BIDANG JASA LAYANAN PENERBANGAN (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 975 K/PDT/2019) - Raras Ayundhani; Anna Maria Tri Anggraini (Jurnal Hukum Adigama, 2020)
Passengers named Regina Goenawan, Sandra Goenawan, Ramona Goenawan, and Julius Chandra when they arrived at Soekarno Hatta Airport wanted to check in at the Air Asia counter for XT 7680 flight types, not allowed by Air Asia on the grounds that the name Regina Goenawan entered in blacklist. Air Asia at that time didn’t provide an explanation of the blacklist. This action is a one-sided flight cancellation. Passengers are suing PT Air Asia Indonesia Extra to the Tangerang District Court to the Cassation level at the Supreme Court. What are the Legal Considerations of Judges at the Tangerang District Court, Banten High Court, the Supreme Court that examined, tried, and decided the case? Is it in accordance with relevant regulations regarding the legal protection of passengers as consumers? The author examines using normative research methods. Research data shows that as law enforcers, the panel of judges in the Judicial Judgment of the Tangerang District Court Nomor 169 / Pdt.G / 2017 / PN. Tng and Banten High Court Nomor 9 / Pdt / 2018 / PT. Btn hasn’t compatibility with related regulations. While the Supreme Court's Decision Nomor 975 K / Pdt / 2019 is in accordance with regulations regarding legal protection of passengers as consumers and airlines. The airlines ignore the transparency of information and the inaccuracy in managing passenger data, the government should make more specific regulations regarding the transparency of information in the field of aviation services as a legal protection against passengers.